"Vittorio Alfieri: éditer, commenter, traduire" - Paris Convention, 16-17 February 2018 (Prassi Ecdotiche della Modernità Letteraria, 2018)
The Seminar Vittorio Alfieri: éditer, commenter, traduire(Parigi, 16th-17th February 2018) was born from the cohoperation between the Université Paris 3 Sorbonne Nouvelle and the ITEM (Institut des Textes & Manuscrits Modernes, CNRS-ENS). It was organized by Christian Del Vento, Enrico Ricceri and Monica Zanardo, and it was focused on edition, comment and translation of Alfieri’s works. In this number of PEML we pubish the lecture given by Lucia Bachelet, For a new critical edition of Alfieri's political treaties: https://riviste.unimi.it/index.php/PEML/article/view/10481